Research Progress on Diagnosis and Treatment of Diarrhea Predominant Irritable Bowel Syndrome in Traditional Chinese Medicine - Luo, Jintao; Liu, Kaijian; Qiao, Huixia; Liu, Xinyu (Journal of Contemporary Medical Practice, 2025)
The pathogenesis of diarrhea predominant irritable bowel syndrome has not yet been fully clarified in western medicine, and symptomatic treatments such as spasmolysis and antidiarrheal are generally used in clinic, which lacks systematicness and long-term effectiveness, and the clinical efficacy of some patients is not ideal. Traditional Chinese medicine has significant advantages in improving clinical symptoms, improving body immunity and improving patients' quality of life through syndrome differentiation and treatment. This article mainly summarizes the etiology and pathogenesis of IBS-D, and the treatment methods and prescriptions, in order to provide some ideas and references for the clinical diagnosis and treatment of IBS-D in TCM.